RESEARCH OF THE PHYTOTOXIC EFFECT OF TEBUCONAZOLE, РROTHIOCONAZOLE, FLUDIOXONYL AND BASED ON THEM PRODUCTS ON THE GERMINATION POWER AND GROWTH OF SEEDLINGS OF WHEAT AND WHITE MUSTARD - Elena А. Saneeva; Ol’ga V. Zorkina; Elena E. Nefed’eva (Siberian Journal of Life Sciences and Agriculture, 2022)
The elaboration of new fungicidal protectants is an urgent issue due to the ability of pathogens to develop resistance. This fact contributes to the constant production of new protectants, so it carries an additional environmental impact. The main problem of development of new fungicides is choice of methods for identifying of optimal combinations and concentrations of fungicides. The optimization of the composition of fungicides is aimed to reduce the amount of active substances due to the synergistic effect. The use of fungicidal preparations with a reduced amount of active substances carries a lower environmental impact and gives a greater economic effect.